Peningkatan Hasil Belajar Peserta Didik Melalui Penerapan Model Problem Based Learning Kelas IV UPTD SDN 01 Jopang Manganti - Restu Mutiara Sari; Syawaluddin Syawaluddin; Deslita Deslita; Puspani Utami Putri; Efnida Efnida; Rio Satria (Jurnal Pendidikan Tuntas, 2024)
Education aims to increase the quantity and quality of students. In the learning process, the selection of appropriate learning methods greatly affects the high and low learning outcomes of students. It is caused by conventional learning methods that do not involve students actively in the learning process. The application of the PBL model is expected to encourage active participation of students in solving real problems so as to improve concept understanding and critical thinking skills. This research uses the type of classroom action research (PTK). The subjects in this study were fourth grade students of UPTD SD Negeri 01 Jopang Manganti, totaling 11 students consisting of 3 male students and 8 female students. Classroom action research was carried out in four cycles, each cycle consisting of one meeting. In this study there are four stages, namely planning, implementation, observation and reflection. Data collection was carried out using observation and written tests. Based on the results of the study, it shows that the average learning outcomes of students have increased. It is known that the KKM value that has been determined from the school is 75. In the research, it is known that 8 students have not completed with a percentage of 73% and 3 students who have completed with a percentage of 27%. In cycle I, there was an increase of 4 students who were complete with a percentage of 40% and students who were not complete with a percentage of 60%. Furthermore, in cycle II it increased by 6 students with a percentage of 55% and 5 students who were not complete with a percentage of 45%. Furthermore, in cycle III it increased by 8 students with a percentage of 72.73% and 3 students who were not complete with a percentage of 27.73%. In cycle IV students reached a complete score with a percentage of 100%. Thus, the Problem Based Learning Model can improve student learning outcomes in PAI subjects at UPTD SDN 01 Jopang Manganti.